THE POSITION OF LOW MALAY SHORT STORIES IN THE HISTORY OF INDONESIAN LITERATURE - Pujiharto Pujiharto; Sudibyo Sudibyo (Humaniora, 2016)
This article tries to determine the factors causing the Low Malay short stories became unaccounted, especially those that were collected in Miss Koelit Koetjing (2005), in the constellation of the history of modern Indonesian literature. To answer these problems, this paper explores the criteria applied by the author of the history of Indonesian literature, comparing it with the Low Malay short stories, and relates them to their cultural historical context.The results showed the reason that Low Malay short stories collected in Miss Koelit Koetjing were not accounted, are caused by the following factors. First, most of the short stories still retain the traditional genres, such as hikayat (saga) and fairy tales, which show the strength of the cultural orientation of the past. Second, the authors of short stories are not natives; the author is not in the sense of the creator, the creator, but a storyteller, just to recount a story that has been there before. Third, short stories were published in newspapers and not in the book form. Fourth, the world of their stories came from diverse cultures and not from the world of the Indonesian archipelago. With a similar reality, it can be concluded that the short stories collected in Miss Koelit Koetjing, in the broad realm of Low Malay literature, is a literary tradition of its own in the constelation history of Indonesian literature.